2006
DOI: 10.1097/01.brs.0000219944.18223.52
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between the Aggrecan Gene and Familial Idiopathic Scoliosis

Abstract: Despite the negative association reported here, further investigation of the gene and its potential association to FIS is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…2 As scoliosis is a phenotypic characteristic of many ECM disorders, such as Marfan syndrome and Ehlers -Danlos syndrome, the hypothesis that a defect within the ECM is the causative factor of idiopathic scoliosis is plausible. Preliminary studies have focused on the genes responsible for the structural components of the ECM system, including COL1A1, 19 COL1A2, 19,20 COL2A1, 19 FBN1, 20 elastin 20 and aggrecan genes; 21,22 however, all the genes were excluded as potential causative factors for idiopathic scoliosis within the study populations. Matrilin-1, a non-collagenous protein, is secreted primarily by chondrocytes and has a role in the assembly of cartilage ECM.…”
Section: Introductionmentioning
confidence: 99%
“…2 As scoliosis is a phenotypic characteristic of many ECM disorders, such as Marfan syndrome and Ehlers -Danlos syndrome, the hypothesis that a defect within the ECM is the causative factor of idiopathic scoliosis is plausible. Preliminary studies have focused on the genes responsible for the structural components of the ECM system, including COL1A1, 19 COL1A2, 19,20 COL2A1, 19 FBN1, 20 elastin 20 and aggrecan genes; 21,22 however, all the genes were excluded as potential causative factors for idiopathic scoliosis within the study populations. Matrilin-1, a non-collagenous protein, is secreted primarily by chondrocytes and has a role in the assembly of cartilage ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that tested associations using microsatellite markers are not listed: Aggrecan, tested in American [18] and Russian [16] cohorts; COL1A1, COL1A2, and COL2A1, tested in 4 Caucasian families with autosomal dominant inheritance [15]; COL1A2, ELN, and FBN1, tested in 11 Caucasian families with autosomal dominant inheritance [14]; and MTNR1A, tested in an American cohort [17] SNP single nucleotide polymorphism* Female cohort…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…The genes encoding fibrillin ( FBN1 ), elastin ( ELN ), collagen I A1 and A2 ( COL1A1 , COL1A2 ), collagen II A1 ( COL2A1 ), and aggrecan ( ACAN ), showed no association with IS on linkage analysis and/or transmission disequilibrium testing [1416, 18]. Interestingly, using 50 informative Italian trios, Montanaro and colleagues [19] showed that an intragenic microsatellite (short tandem repeat) polymorphism in the 3′ untranslated region of the matrilin 1 gene ( MATN1 ) was associated with adolescent IS.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…IS-related susceptible genes currently being researched include melatonin receptor 1A [14], melatonin receptor 1B [15], Matrilin-1 (MATN1) [16], γ-1-syntrophin (SNTG1) [17], COL1A1 [18], COL1A2, COL2A1, elastic fibre [19] and aggrecan [20] genes. Studies showed that these genes are related with IS but cannot explain all IS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that these genes are related with IS but cannot explain all IS patients. Chromosomal regions involved in IS susceptibility include 6p, 10q, 18q [21], 6p, 6q, 17p11.2 [5], 8q [22], 9q, 16q [23], 19p13 [3], 19p13.3 [9], 15q25-26 [20], 9q31.2, 9q34.2, 17q25.3-qtel [24], 12p [25] and Xq23-26 [26]. There are considerable numbers of genes in these foci.…”
Section: Introductionmentioning
confidence: 99%